Enterococcus durans infection and diarrhea in Thoroughbred foals - Natasha J. Williams; Nathan M. Slovis; Nimet S. Browne; Mats H. T. Troedsson; Steeve Giguėre; Jorge A. Hernandez (Journal of Veterinary Internal Medicine, 2022)
Abstract Background Diarrhea remains an important cause of morbidity and mortality in neonatal foals, and correct identification of etiologic agents is essential for effective disease management. Objective To examine the association between diarrhea and detection of Enterococcus durans or other enteropathogens in neonatal foals on 1 breeding farm in Kentucky, USA. Animals Fifty‐nine Thoroughbred foals and their broodmares. Methods Prospective observational study. Study foals and broodmares were sampled and tested for E. durans and other enteropathogens during the first 10 days after foaling. The frequency of foals in which E. durans or other enteropathogens was compared between foals with or without diarrhea. Results Seven of 59 foals developed diarrhea. The frequency of foals with E. durans infection was higher in foals with diarrhea 5/7 (71%), compared to foals without diarrhea 0/51 (0%; P < .01). Detection of E. durans in foals was associated with detection of E. durans in broodmares; in 2/7 (29%) foals with diarrhea, the 2 broodmares tested positive for E. durans, and, in 51/51 (100%) foals without diarrhea, all broodmares tested negative to E. durans (P = .01). Based on the spatial and temporal distribution of foals with diarrhea, 5 of 6 additional cases of diarrhea were attributed to lateral transmission of E. durans infection. Conclusions and Clinical Importance Detection of E. durans was associated with diarrhea in foals. Implementation of enhanced biosecurity measures might mitigate disease transmission associated with E. durans infection in foals.